Effect of Intervention Guidelines on Nurses' Performance Regarding Patient's Outcome Post Glaucoma Surgery (Journal of Pharmaceutical Negative Results, 2023)
Background: Glaucoma is a leading cause of irreversible visual impairment worldwide. Ophthalmic nurses play a critical role in managing glaucoma surgery patients. Aim of study: This study aimed to evaluate the effect of intervention guidelines on nurses' performance regarding patient's outcome post glaucoma surgery at Zagazig University Hospitals. Design: A quasi experimental design was utilized in this study. Setting: Data was collected from department of ophthalmology and ophthalmology outpatient clinic at Zagazig University Hospitals. Subjects: The study was conducted on Convenience sample of all available nurses working in ophthalmology department and caring for patients with glaucoma surgery (40 nurses), and two groups of patients (40 patients) for each. Tools of data collection: Three tools were used for collection of data, first, structured interview questionnaire for nurses, Second tool was an observational check list to assess nurses’ practice regarding patients with glaucoma surgery, Third tool was patient assessment questionnaire to assess patient outcome post glaucoma surgery. Results: 72% of nurses aged below 45 years, 95% of them were married, 77% of them had diploma in nursing, 57% of them had more than ten years of experience in ophthalmology department, 95.5% of them didn’t have training course in the care of glaucoma surgery patient. There were statistically significant improvements in mean differences scores of studied nurses' knowledge and practice regarding glaucoma post intervention compared to pre intervention. There was statistically significant relation between satisfactory nurses’ practice and their qualifications. There was statistically significant relation between nurses’ knowledge, practice and patients' post operative outcome post intervention. There was statistically positive correlation between total scores of nurses’ knowledge and practice, and post operative outcome. Conclusion: It can be concluded that the intervention guidelines significantly improved nurses' knowledge and practice about glaucoma with a sustained improvement in the patients’ outcomes and reducing postoperative complications. Recommendations: It is recommended that periodic evaluation and validation of the training given and training programs should be included both theoretical and practical.